Pengaruh Experiental Marketing Dan Kualitas Pelayanan Terhadap Minat Berkunjung Kembali Di Jawa Timur Park I - Elis, Diana Olivia Male (Sekolah Tinggi Pariwisata Sahid Surakarta, 2025)
This study aims to analyze the influence of experiential marketing and service quality on tourists’ revisit intention to the Jatim Park 1 destination in Batu City, East Java. As one of the most popular educational tourism destinations in Indonesia, Jatim Park 1 faces challenges in maintaining visitor loyalty amidst the increasingly competitive tourism industry. Experiential marketing is considered capable of creating enjoyable and memorable experiences through sensory, emotional, cognitive, behavioral, and social relationship elements. Meanwhile, service quality reflects the destination’s ability to meet visitor expectations through friendly, responsive services and adequate physical facilities. This research employs a quantitative approach with an explanatory design. The respondents were tourists who had visited Jatim Park 1 more than once within the past three years. The results indicate that both experiential marketing and service quality have a positive influence on revisit intention. Experiential marketing proves to have a more dominant influence, but service quality still plays an important role in shaping visitor satisfaction and perceptions. Therefore, experience-based marketing strategies supported by high-quality services are considered effective in enhancing tourist loyalty and can serve as a reference for the development of other tourism destinations.